Tear production, intraocular pressure and conjunctival microbiota, cytology and histology of New Zealand rabbits (Oryctolagus cuniculus) - Oriá,Arianne P. (2014)
The purpose of this study was to establish reference values for selected ophthalmic diagnostic tests in New Zealand rabbits (Oryctolagus cuniculus). A total of 22 adult male rabbits were used. The ophthalmic tests included evaluation of tear production with Schirmer tear test 1(STT1) and Endodontic absorbent paper point tear test (EAPPTT) using two different commercial brand materials. Applanation tonometry, Culture of the conjunctival bacterial flora, , conjunctival cytology and conjunctival histology were also performed. Mean (±SD) for STT1, EAPPTTa, EAPPTTb and IOP was 7.27±2.51mm/min, 12.43±1.69mm/min, 15.24±2.07mm/min, 12.89±2.80mm Hg, respectively. Staphylococcus epidermidis, Staphylococcus sp. and Bacillus sp. were predominant. The cytological evaluation revealed the presence columnar epithelial cells, superficial squamous keratinized cells, lymphocytes, heterophils, red blood cells, mucus and bacteria. The histological analysis revealed a stratified epithelium, characterized by the presence of columnar epithelial cells with a large number of goblet cells. The reported data can be used for therapeutic or experimental purposes.